A Semiotic Analysis in Victoria Secret Product Advertisements - Desak Putu Eka Pratiwi; I Gede Dayuh Suryantara; I Dewa Ayu Devi Maharani Santika (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2022)
This study concern with semiotic analysis and explains the meanings that are conveyed by verbal and non verbalsign found in Victoria Secret Product Advertisements. In analyzing this study the method that used was descriptive qualitative method to conduct a clear and well organized descriptions bout the problem. In regards of the analysis there are two theories and one supported theory applied in this research namely theory of Saussure (1983) in analyzing signifier and signified of the sign. The second theory is denotation and connotation meaning by Barthes (1986). And the last supported theory by Wierzbicka (1996) theory of colorterms. The verbal signs is to convey the information from the advertiser to the readers, meanwhile non verbalsigns used to make the advertisement look cool, attractive and impressive, but still contained the meaning that related to the product that offered in advertisements. The researcher found there are 22 data of verbal and non verbal signs Which also carried two types of meaning, those are denotation and connotation meaning Both of verbal and non verbal signs contained connotative and denotative meaning. Verbal sign consist of explanation of the product and non verbal sign consist of picture and color.